New legal rulings related to Beasts of cattle in Zakat - AlShepan, Ibraheem Mohamed (Journal of Islamic Sciences, 2022)
This research dealt with the most important emerging jurisprudential issues related to cattle، especially in the chapter on zakat. As well as the comparative scientific method، and I concluded in this research the following results: 1- The correct one from the two scholars’ sayings is that the sum is considered a condition for the obligation of zakat on livestock، and that the regulation of the sum is what is meant by the fertilization، offspring، growth، ghee and the like. The tax is not considered if the intention is for riding، loading، eating its meat، or for hospitality، and there is no zakat on it. 2- Permissibility of different prices for zakat on livestock، which are determined by the guardian from one region to another; Because that is due to the interest that is estimated by the guardian، and what is achieved by paying zakat and reaching those who are entitled to it.